Intrapartum Management of Women With Human Immunodeficiency Virus Infection. Issue 1 (January 2019) - Wisner, Kirsten
Abstract : New guidelines for caring for women during labor and birth who are infected with HIV have been published. Our maternity nursing expert, Kirsten Wisner, offers a summary of the clinical implications for perinatal nurses.